The Dancer and the Dance Christopher Wheeldon's new Swan Lake in Philadelphia - Felciano, Rita (Dance Books Ltd., Alton,Hampshire (UK), 2004)
Christopher Wheeldon for the Pennsylvania Ballet. Wheeldon topped this with a Can-Can straight out of a Toulouse-Lautrec, the madame of the house included. PALABRAS CLAVE: Christopher Wheeldon, Swan Lake, Pennsylvania Ballet.
Dentro del apartado "It's Always Swan Lake".